Engineering Design of a Device for Shearing Metal Sheets in a Non-conventional Way - Moravec, Ján; Blatnický, Miroslav; Dižo, Ján (Manufacturing Technology Journal, 2018)
This constribution presents the engineering design of the non-conventional shearing device, which uses for the operation the magnetic field. There is a prototype of the device designed and constructed in laboratory conditions. There are presented all relevant and necessary data of this shearing device supported by figures and scheme. The principle of the device operation consists in the fact that a sheet passes through feed rollers into the shearing position, i.e. into the position between two blades. Lower is fixed and the upper is guided in rails and controlled by means of springs. After the material dividing the electric circuit is interrupted and the moving blade returns into the starting position due to spring's action. This process of metal shearing can be quite simply automated. We have performed same experimental works using this device. There were sheared same sheet samples and the comparision of surfaces are shown. The use of our our device has proven to be appropriate for shearing sheets made of aluminium alloys with the thickness of 0.3 mm.
Keywords: Shearing; Non-conventional method; Magnetic field; Differential equation